2020
DOI: 10.1177/1358863x20937665
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of peripheral arterial and venous Doppler waveforms: A consensus statement from the Society for Vascular Medicine and Society for Vascular Ultrasound

Abstract: This expert consensus statement on the interpretation of peripheral arterial and venous spectral Doppler waveforms was jointly commissioned by the Society for Vascular Medicine (SVM) and the Society for Vascular Ultrasound (SVU). The consensus statement proposes a standardized nomenclature for arterial and venous spectral Doppler waveforms using a framework of key major descriptors and additional modifier terms. These key major descriptors and additional modifier terms are presented alongside representative Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 42 publications
2
66
0
3
Order By: Relevance
“…In our screening studies at 19-23 and 35-37 weeks' gestation, we found that, in pregnancies which subsequently developed PE, compared to those which remained normotensive, the ophthalmic artery pulsatility index was not significantly different but the PSV ratio was increased 15,16 . The first systolic component of an arterial waveform is produced by the contraction of the left ventricle, whereas the second systolic wave is a reflected one 28 . The observed increase in the velocity of the second compared to the first systolic waveform in the ophthalmic artery is not indicative of increased ophthalmic or cerebral perfusion but rather of increased peripheral resistance.…”
Section: Interpretation Of Results and Comparison With Findings Of Previous Studiesmentioning
confidence: 99%
“…In our screening studies at 19-23 and 35-37 weeks' gestation, we found that, in pregnancies which subsequently developed PE, compared to those which remained normotensive, the ophthalmic artery pulsatility index was not significantly different but the PSV ratio was increased 15,16 . The first systolic component of an arterial waveform is produced by the contraction of the left ventricle, whereas the second systolic wave is a reflected one 28 . The observed increase in the velocity of the second compared to the first systolic waveform in the ophthalmic artery is not indicative of increased ophthalmic or cerebral perfusion but rather of increased peripheral resistance.…”
Section: Interpretation Of Results and Comparison With Findings Of Previous Studiesmentioning
confidence: 99%
“…The strength of our study compared to previous work is to evaluate the reliability of this classification over a large and homogenous sample in terms of occupation and experience. A first American consensus about Doppler waveform interpretation has just been released in July 2020 to try to clarify the way of reporting Doppler waveforms in clinical practice but it did not address the reliability of Doppler waveform analysis (17).…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, we have published national and international consensus statements on behalf of SVM, including the 2019 international consensus on FMD (in partnership with the European Society for Hypertension) and the 2020 consensus on Doppler waveform nomenclature (in partnership with the Society for Vascular Ultrasound) published in this issue of our journal. 8,9 Last, but not least, we initiated the SVM Communication Pages, also known as the 'blue pages'. This section serves as a forum for updates on societal initiatives, a spotlight on junior and senior members of the Society, and gives attention to timely topics in our field.…”
Section: -2019 Accomplishmentsmentioning
confidence: 99%